Operating gravitational wave detectors far from equilibrium. (10th July 2018) - Neri, Igor; López-Suárez, Miquel; Gammaitoni, Luca
Abstract: Tiny vibrations of mechanical structures are a limiting cause in a number of high sensitivity measurement apparatus, chief among them the most sensitive displacement apparatus on Earth: the gravitational wave interferometer. Such a device is usually operated at equilibrium and small fluctuations are perceived as noise that sets a lower limit to the detection capabilities. In this work we present an approach aimed at operating the interferometer out of equilibrium. We show that selective cooling of a frequency range of the mechanical structure is able to positively impact the measurement sensitivity, on that range. Experiments conducted on thin silica membranes show promising results for the implementation of such a technique.